Pemberdayaan Kelompok Tani Melalui Inovasi Pestisida Nabati Daun Pepaya Dalam Penurunan Kemiskinan Ekstrem - Anggina Khairani Harahap; Irhamsah Putra Pasaribu; Erwan Efendi (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
As an agrarian country, Indonesia faces serious challenges in pest control, where dependence on synthetic pesticides has led to multidimensional negative impacts on the environment, human health, and ecosystem balance. This practice is also contrary to the principles of maqashid sharia in Islamic economics, which emphasizes the protection of life, the environment, and the preservation of natural resources. This study aims to explore alternative pest control methods that are environmentally friendly, sustainable, and in accordance with Sharia values, through the use of plant-based pesticides from papaya leaves (Carica papaya L.). The methods used in this Real Work Lecture (KKN) activity included observation of agricultural conditions in the field, as well as socialization and direct demonstration of the manufacture of vegetable pesticides to farmer groups in Bandar Manik Village, Simalungun Regency. The results of the activity show that papaya leaf plant pesticides are not only effective in controlling pests, but are also easy to make, inexpensive, biodegradable, and do not cause harmful residues. From the perspective of Islamic economics, the application of plant-based pesticides is in line with the principles of maqasyid sharia, especially in preserving the environment (hifzh al-bi’ah) and human welfare, as well as supporting the realization of an agricultural system, namely, halalan thayyiban. This program is expected to be a sustainable solution for farmers to reduce their dependence on chemical pesticides while optimizing local potential in accordance with Islamic values.